Incidence and impact of cardiac cachexia in valvular surgery - Thitipong Tepsuwan (2018)
Cardiac cachexia is a wasting feature of advanced heart failure, which is due to several etiologies and associated with a poor prognosis. This study assessed the incidence and impact of cardiac cachexia retrospectively in 353 patients who underwent valve surgery from June 2005 to June 2006. Using 80% of ideal body weight as a cut-off point, 46 (13%) of these patients were considered to have cardiac cachexia. Patients with cachexia were predominantly male with more underlying diseases and a lower body mass index than those without cachexia. The New York Heart Association functional class was significantly worse in patients with cachexia (class III/IV: 54.4% vs. 21.2%) and they had greater incidences of active infective endocarditis (21.7% vs. 5.2%) and tricuspid regurgitation (41.3% vs. 21.8%) compared to those with normal body weight. The cachexia group had significantly longer postoperative hospitalization and more complications (37% vs. 21.5%); perioperative mortality tended to be higher (6.5% vs. 2.3%) although not statistically significant. Cardiac cachexia remains an important problem in patients undergoing valve surgery, which indicates end-staged disease, and contributes to poor perioperative outcomes. Special care and attention are needed in this particular group of patients. © 2009 SAGE Publications.